2013
DOI: 10.1021/jm401118f
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Dissection of Linear Motif Recognition by the E. coli Sliding Clamp

Abstract: Protein-protein interactions based on linear motif (LM) recognition play roles in many cell regulatory processes. The E. coli sliding clamp is a protein mediator of replisome formation, which uses a common surface pocket composed of two subsites (I and II) to interact with LMs in multiple binding partners. A structural and thermodynamic dissection of sliding clamp-LM recognition has been performed, providing support for a sequential binding model. According to the model, a hydrophobic C-terminal LM dipeptide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(83 citation statements)
references
References 48 publications
7
76
0
Order By: Relevance
“…Interestingly, the orientation of EcM 362 differs between the apo and peptide bound structures of Ec SC 10 and has been shown to be in dynamic equilibrium between these two conformations. 11 These essential interactions are maintained in all SC/ peptides complexes studied, whether the structural information is available experimentally or by docking of the native peptide on the apo SC structures (see SI.12A,B,E). However, the changes in sequence between the different SC may affect the detailed energetic balance between the different interaction sites.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the orientation of EcM 362 differs between the apo and peptide bound structures of Ec SC 10 and has been shown to be in dynamic equilibrium between these two conformations. 11 These essential interactions are maintained in all SC/ peptides complexes studied, whether the structural information is available experimentally or by docking of the native peptide on the apo SC structures (see SI.12A,B,E). However, the changes in sequence between the different SC may affect the detailed energetic balance between the different interaction sites.…”
Section: ■ Discussionmentioning
confidence: 99%
“…10 Recently, it was suggested that peptide binding onto Ec SC could occur via a two steps process, with an initial interaction in SS1, followed by the binding in SS2. 11 Because SC is a central element for the physiological functions of enzymes involved in DNA metabolism 4 and their trafficking, 12,13 the binding pocket has been considered as a target for the development of new antibacterial drugs. 5,9,14 Several studies have explored this potentiality either by screening a chemical bank 14 or by a structured-based design approach, opening the way for structure−activity studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Linear motif interactions with  Eco have been extensively characterized (Wijffels et al, 2004;Georgescu et al, 2008b;Wolff et al, 2011;Yin et al, 2013), and interactions between linear motif peptides and  from Mycobacterium tuberculosis, Bacillus subtilis, Staphylococcus aureus, and P. aeruginosa, while less studied, have been reported (Gui et al, 2011;Wolff et al, 2014). In the present study, binding of a fluorescently labeled linear motif-consensus peptide (5FAM-Q1L2D3L4F5-OH; "P1") to the bacterial  clamps studied by fluorescence polarization (FP).…”
Section: Consensus Peptide Interactions With Linear Motif-binding Pocmentioning
confidence: 91%
“…FP experiments were carried out as described previously (Yin et al, 2013(Yin et al, , 2014(Yin et al, , 2015. The fluorescent peptides, at 10 nM concentration, and proteins were in 10 mM HEPES buffer, pH 7.4, 1 mM EDTA, 1 mM dithiothreitol, 0.07% (v/v) nonidet-P40 and 5% (v/v) DMSO.…”
Section: Fluorescence Polarization Assaysmentioning
confidence: 99%
See 1 more Smart Citation